APLIKASI LARUTAN PENGAWET TERHADAP KUALITAS BUNGA POTONG KRISAN (Chrysanthemum Sp.) - Randika A. Nento; Diane Sophie Tiwow; Sofia L. Demmassabu (COCOS, 2017)
ABSTRACT The research aims to studies the use of a preservative solution of and to get composition a preservative solution of appropriate on the quality of cut flowers chrysanthemum. Research conducted at the laboratory of Plants Science, Faculty of Agriculture, Sam Ratulangi University Manado in Juni until July 2016. The experimental design used was a completely randomized design with five replications. The composition of preservative solution A: water 1000 ml; B: sugar 25 g/l + lime water 1 ml/l + chlorox 1 ml/l, C: sugar 50 g/l + lime water 2 ml/l + chlorox 1 ml/l, D: sugar 75 g/l + lime water 3 ml/l + chlorox 1 ml/l, E: sugar 100 g/l + lime water 4 ml/l + chlorox 1 ml/l, F: sugar 125 g/l + lime water 5 ml/l + chlorox 1 ml/l, G: sugar 150 g/l + lime water 6 ml/l + chlorox 1 ml/l. Observed variables were the total of absorbed solution, vaselife, when the flowers were wilt and flowers color. The results showed the tretment effect of the composition of preservative solutions give effect of the total absorbed solution 184,8 ml, 27,2 vaselife day period, when the flower were wilt 24,2 days and flowers color.Â  Keywords : cut flowers, chrisanthemum (Chrysanthemum Sp.), preservative solution, vaselife